2021
DOI: 10.1111/jcpe.13583
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fixation enhances guided bone regeneration in standardized calvarial defects: A pre‐clinical study

Abstract: Aim: To determine whether collagen membrane (CM) fixation enhances guided bone regeneration in standardized defects.Materials and Methods: Four 8-mm-diameter defects were surgically made in eight rabbit calvaria, and randomly allocated into four groups: control (empty), unfixed-CM, fixed-CM, and unfixed-CM with bone graft (BG + CM) (positive control). After 1and 4-week healing periods, the animals were sacrificed and quantitative reverse transcription polymerase chain reaction, micro-computed tomography, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…To circumvent this problem, techniques to immobilize the collagen membrane have been used, including membrane‐stabilizing sutures, bone tacks, and titanium pins (Porcaro et al, 2017). Membrane fixation using bone tacks has been shown to enhance not only the width of the sites grafted with particulate bone substitute (Mir‐Mari et al, 2016; Naenni, Berner, et al, 2019) but also the expression of osteogenic factors (An et al, 2021). These bone tacks, however, can increase the duration of surgery, cost of treatment, and difficulty of the augmentation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this problem, techniques to immobilize the collagen membrane have been used, including membrane‐stabilizing sutures, bone tacks, and titanium pins (Porcaro et al, 2017). Membrane fixation using bone tacks has been shown to enhance not only the width of the sites grafted with particulate bone substitute (Mir‐Mari et al, 2016; Naenni, Berner, et al, 2019) but also the expression of osteogenic factors (An et al, 2021). These bone tacks, however, can increase the duration of surgery, cost of treatment, and difficulty of the augmentation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Том 21 № 3. 2022 Таким образом, результаты исследования, полученные авторами через 12 месяцев после оперативного лечения, позволяют обоснованно присоединиться к мнению отечественных и зарубежных коллег, использующих дополнительную фиксацию пародонтологической мембраны пинами, особенно, как представлено в данном исследовании, при дефектах сложной конфигурации [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: For Citationunclassified
“…Up to now, collagen membrane is the one of favorable barrier materials used in GTR operation, as removal surgery and additional pain or infection are associated with the other non-resorbable membranes [14,15]. However, the reconstruction outcomes are significantly depended on the stability of collagen membrane and regeneration space [16][17][18]. Hence, the barrier membrane is frequently used combined with bone grafts, as such bone Conclusions: Our results suggested that such modularized hierarchical architectures have excellent potential as a next-generation oral implants, and this precisely tuned guided tissue regeneration route offer an opportunity for improving periodontal damage reconstruction and reducing operation sensitivity.…”
Section: Introductionmentioning
confidence: 99%